Teachers’ Sense-making of English Guru Penggerak in Implementing Deep Learning through Mindful, Meaningful, Joyful Learning Priciples - Adelmi Kurniawati Ds; Hasanuddin Fatsah; Muziatun Mukadji; Moon Hidayati Otoluwa; Sartin Miolo (Universitas Islam Negeri Palopo, 2026)
This study examines English Guru Penggerak teachers' perceptions of Deep Learning through the Mindful, Meaningful, and Joyful (MMJ) framework in junior high school English classrooms in North Gorontalo Regency. In this study, Deep Learning refers to a pedagogical policy within the Indonesian education system rather than artificial intelligence or machine learning. The study addresses two research questions: how teachers perceive Deep Learning through the MMJ principles and how they describe their readiness to implement them. A descriptive qualitative design was employed involving eight English Guru Penggerak teachers. Data were collected through semi-structured interviews and supported by document analysis of teaching modules, worksheets, and assessment instruments. The data were analyzed using thematic analysis, including coding, cross-participant comparison, and document triangulation. The findings indicate that teachers generally perceived MMJ positively and considered it relevant to English language learning. They associated the framework with a safer classroom climate, greater student participation, stronger motivation, and more meaningful learning experiences. However, teachers demonstrated varying levels of conceptual understanding, with some still developing their understanding of MMJ while others articulated its principles more comprehensively. Teachers also showed uneven readiness to implement the framework. Pedagogical readiness was reflected in contextual learning tasks, reflective practices, and interactive classroom activities, whereas assessment readiness remained the weakest dimension. In addition, leadership support, professional learning communities, academic supervision, infrastructure, workload, and time allocation influenced implementation. The study concludes that MMJ implementation remains vulnerable to “joyful but shallow” enactment when enjoyable learning activities are not supported by purposeful awareness, meaningful learning, reflection, feedback, and evidence of student learning progress.